Gaze control in one versus one defensive situations in soccer players with various levels of expertise - Krzepota, J.; Stepinski, M.; Zwierko, T. (Perceptual and Motor Skills, 2016)
Experienced and less experienced soccer players were compared in terms of their gaze behavior (number of fixations, fixation duration, number of fixation regions, and distribution of fixations across specific regions) during frontal 1 vs. 1 defensive situations. Twenty-four men (eight experienced soccer players, eight less experienced players and eight non-players) watched 20 video clips. Gaze behavior was registered with an Eye Tracking System. The video scenes were analyzed frame-by-frame. Significant main effect of the group (experience) was observed for the number of fixation regions. Experienced soccer players had a lower number of fixation regions than the non-soccer players. Moreover, the former group presented with significantly larger percentage of fixations in the ball/foot region. These findings suggest that experienced players may use a more efficient search strategy than novices, involving fixation on a lesser number of areas in specific locations. ABSTRACT FROM AUTHOR